Does Career Development Foster Organizational Citizenship Behavior? The Mediating Influence of Job Satisfaction - Grace Kusumawardhani; Siera Syailendra; Tutik Yuliani (Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
This study investigates the relationship between career development, job satisfaction, and organizational citizenship behavior (OCB) by testing the mediating role of job satisfaction. Using a quantitative explanatory design, data were collected from 100 permanent employees of PT Bank Rakyat Indonesia in Bekasi and analyzed with Structural Equation Modeling–Partial Least Squares (SEM–PLS). The findings reveal that career development has a strong and positive effect on job satisfaction but does not directly influence OCB. Instead, job satisfaction significantly predicts OCB and mediates the relationship between career development and OCB. These results emphasize that career development initiatives can only foster citizenship behaviors when they enhance employees’ satisfaction with their jobs. Theoretically, the study strengthens Social Exchange Theory by highlighting job satisfaction as a critical attitudinal mechanism. Practically, the results suggest that organizations should align career development programs with employees’ psychological needs to increase satisfaction and, consequently, stimulate extra-role behaviors. Future studies are encouraged to extend the analysis across industries and adopt longitudinal designs to validate the causal pathways identified.